Material Source and Waste Taxes in Competitive Equilibrium - Reyer Gerlagh; Etienne Lorang (CESifo GmbH, 2024)
We develop a framework for the representation of material flows in competitive equilibrium. Material balances track material flows, which adjust endogenously to economic transactions. We assume negative environmental effects of resource extraction and waste deposition and show that taxing resource extraction restores efficiency. Taxing waste, where generated, only restores efficiency if producers minimize users' costs of their products, or if there is a dense set of goods with varied material content. We set up the general model structure and use a stylized 3-sector model for illustration. Finally we develop a quantitative stylized assessment of global steel and fossil fuel use.
Keywords: H21; Q29; 330; material balances; material policies; waste policies; upstream versus downstream